FENOMENA PENURUNAN ANGKA PERNIKAHAN DAN PERKEMBANGAN BUDAYA OMIAI DI JEPANG - Budi Mulyadi (Diponegoro University, 2018)
This paper entitled The Phenomenon of Decline in Marriage rates And Matchmaking Culture Development. The main goal of this article is to know the phenomenon of decline in marriage rates and matchmaking culture development in Japan.This reserach uses field research. Main methode are observation and interpretation.This paper shows that one of the factor behind the marriage rtaes decline in Japan is the relatively new-found